Single or dual experimental infections with Vibrio aestuarianus and OsHV-1 in diploid and triploid Crassostrea gigas at the spat, juvenile and adult stages - Azema, Patrick; Travers, Marie-agnes; Benabdelmouna, Abdellah; Degremont, Lionel (Journal of Invertebrate Pathology, 2016)
French production of the Pacific cupped oyster, Crassostrea gigas, is currently threatened by two pathogens, OsHV-1 and V. aestuarianus. While oysters selected for their higher resistance to OsHV-1 are now available for the industry, the impact of V. aestuarianus on such oysters is unknown, especially for triploids. In addition, experimental infection has used the virus or the bacteria alone, but there have been no investigations of dual exposure to these pathogens. This study is the first report of single or dual exposure in spat (Spat1 and Spat2), juvenile and adult naïve oysters. For each of the two stocks evaluated, unselected oysters and oysters selected for their higher resistance to OsHV-1 infection were tested, as well as their triploid siblings of the selected oysters produced using cytochalasin B. We confirmed that resistance to OsHV-1 infection and susceptibility to V. aestuarianus increased with age and size, although selected oysters were not significantly impacted by OsHV-1 whatever their ploidy, size or age. We found different mortality patterns depending on the pathogen tested. The mortality pattern was similar for oysters exposed to OsHV-1 or to both pathogens in the Spat1 trial (4 months old and 1.9 g). The mortality pattern was similar for oysters exposed to V. aestuarianus or to both pathogens in the Adult trial (25 months old and 63.1 g). Surprisingly, mortality was much higher (ranging from 75.9% to 100%), in particular for the selected oysters, for the Spat2 (8 months old/3.9 g) and Juvenile trials (16 months old/18.4 g) given a dual exposure, regardless of the level of selection for OsHV-1 and the ploidy state. Our findings highlight an important threat for oyster farmers: oysters exposed to both pathogens could experience dramatic mortality rates, even in oysters selected for their higher resistance to OsHV-1. Finally, our study demonstrated for the first time that triploid oysters were more susceptible to experimental challenges with V. aestuarianus at the spat stage than their diploid ...